Synthesis, Optimization, Property, Characterization, and Application of Dialdehyde Cross-Linking Guar Gum - Tang Hongbo; Li Yanping; Zhang Wen; Dong Siqing (International Journal of Polymer Science)
Dialdehyde cross-linking guar gum (DCLGG), as a novel material, was synthesized using phosphorus oxychloride as a cross-linking reagent, sodium periodate as an oxidant, and ethanol as a solvent through keeping the original particle form of guar gum. The process parameters such as the reaction temperature, reaction time, pH, amount of sodium periodate, and amount of ethanol were optimized by the response surface methodology in order to obtain the regression model of the oxidization. The covalent binding of L-asparagine onto the surfaces of DCLGG was further investigated. The results showed that the best technological conditions for preparing DCLGG were as follows: reaction temperature = 40°C, reaction time = 3.0 h, pH = 4.0, and amount of ethanol = 74.5%. The swelling power of DCLGG was intermediate between cross-linking guar gum and dialdehyde guar gum. The cross-linking and dialdehyde oxidization reduced the viscosity of GG. The cross-liking reduced the melting enthalpy of GG. However, the oxidization increased melting enthalpy of ACLGG. The thermal stability of GG was increased by cross-linking or oxidization. The variation of the onset decomposition temperature and end decomposition temperature of GG was not consistent with thermal stability of GG. L-asparagine could be chemically bound well by DCLGG through forming Schiff base under the weak acidity. The maximum adsorption capacity of L-asparagine on DCLGG with aldehyde content of 56.2% reached 21.9 mg/g.